Nonlinear radiation on Maxwell fluid in a convective heat transfer with viscous dissipation and activation energy. Issue 7 (5th July 2021) - Gangadhar, Kotha; Vijayakumar, D.; Thangavelu, Kannan
Abstract: The present analysis addresses linear and nonlinear radiation effects in hydrodynamic viscous Maxwell fluid flow on a unidirectional stretching surface through viscous dissipation. The relaxation effect is considered in the mathematical model, which elucidates mass transport mechanisms under binary chemical reaction and activation energy. Mathematical modeling contains nonlinear partial differential equations using boundary conditions. Appropriate transformations convert the partial differential equations into ordinary differential equations. Numerical solutions for regular differential equations are brought by Runge–Kutta–Fehlberg numerical quadrature and a shooting method with a tolerance level of 10 −9 . The influence of physical variables, such as Deborah relaxation number, rotation parameter, Biot number, activation energy parameter, reaction rate parameter, Eckert number, and Prandtl number are investigated. Increasing the Biot number improves the temperature region in the boundary layer. With high rotation, the increasing Deborah number enhances the fluid temperature substantially throughout the boundary layer.